Il grottesco tra Il Trovatore e La Traviata (Itinera, 2014)
The grotesque represents in a certain way the leading form of ugly since the latter became a too general concept to serve as an effective explicatory principle. Starting from Rosenkrantz’s conception of the grotesque, with a view to Kosik’s thesis of the decline of the tragic in favor of the grotesque during the nineteenth century, this article explores the presence and the modes of this aesthetic category in some of Verdi’s masterpieces: Il Trovatore and La Traviata.